MRI Predictors Of Left Ventricle Diastolic Dysfunction (Texas Journal of Medical Science, 2024)
Non-invasive assessment of diastolic dysfunction remains challenging, and this study aims to identify the most informative parameters of cardiovascular magnetic resonance (CMR) for assessing left ventricular diastolic dysfunction (LVDD) OBJECTIVE: To study MRI parameters as predictors of left ventricular diastolic dysfunction (LVDD) in patients with suspected heart failure. PATIENTS AND METHODS. The study included 39 patients with CHF, 25 were men (61%), and the average age of patients was 48.12 ± 16.79 years. RESULTS. The enlarged LA dimensions have diagnostic accuracy according to our data for the detection of diastolic dysfunction (DD). Tissue tracking and tissue phase mapping (TRM) reveal impaired diastolic deformity of the basal-lateral wall in DD+ as a direct sign of DD.